Analysis of the active ingredients and health applications of cistanche - Zhou, Shiqi; Feng, Duo; Zhou, Yaxi; Duan, Hao; Jiang, Yongjun; Yan, Wenjie (Frontiers in Nutrition, 2023)
Cistanche is a tonic Chinese medicine commonly used in traditional Chinese medicine, with 2016, CFSA through the alxa desert cistanche safety evaluation, cistanche began to officially enter the food field. At present, the research on cistanche mainly focuses on the extraction, isolation and purification and pharmacological effects, and its pharmacological effects such as neuroprotective effects, immunomodulation, antioxidant anticancer and hepatoprotective liver protection have attracted the attention of researchers. This review mainly reviews the research status, chemical composition and health benefits, analyzes its application prospects in food, and aims to provide certain theoretical support for the safe application of cistanche in functional food.